Association between Self-Esteem and Smartphone Addiction: The Mediating Role of Self-Control - Rustamov, Elnur; Musayeva, Tunzala; Xalilova, Xalida; Ismayilova, Gultekin; Nahmatova, Ulviyya (Technium Social Sciences Journal, 2023)
The aim of this study was to investigate whether self-control acts as a mediator in the connection between self-esteem and smartphone addiction in a sizable group of adults (N = 1118; age range = 18 to 63 years) residing in various regions of Azerbaijan. The findings revealed a positive association between participants' self-esteem and their self-control, while their level of smartphone addiction exhibited a negative association with self-esteem and self-control. The results obtained from structural equation modeling indicated that self-control fully mediated the relationship between self-esteem and smartphone addiction. Thus, there was a statistically significant indirect impact of self-esteem on smartphone addiction through self-control.